Characterization of patients with chronic low back pain treated with transforaminal epidural injection - Velasco, Hugo Leonel; Chaparro, Walter; Alba, Angie Katherine; Chaparro, Laura (Revista Colombiana de Ortopedia y Traumatología, 2022)
Introduction: Through this study, the clinical and demographic characterization of patients with chronic low back pain operated on with transforaminal epidural steroid injection will be carried out in a fourth level hospital. Materials and methods: A retrospective analytical study of longitudinal temporality was carried out, which included 85 adult patients with chronic low back pain operated on with transfora- minal injection from January 1, 2020 to March 31, 2021. Results: Fifty-three adults (62.4%) were women and 32 (37.6) were men. On average, the age of these individuals was 54 ± 14 years. In 37 cases (43.5%) it was performed bilaterally, and 42 individuals (49.4%) required this type of injection at three lumbar levels. The mean of related symptoms was 24.37 ± 23.5 months. As triggering etiology, 33 individuals (38.8%) had degene- rative disc disease, 25 (29.4%) due to spondyloarthrosis, 16 (18.8%) due to spondylolisthesis. In relation to subjective low back pain, a decrease of −4.1±3.4 (CV=82.1%) (p=0.00) was recorded. Discussion: Transforaminal epidural steroid injection in patients with chronic low back pain is a safe and minimally invasive procedure, which during the period of time studied did not present complications or subsequent hospitalization. The majority of the intervened population corresponds to women between 35 and 55 years of age. A decrease in subjective low back pain was observed after one month of performing this procedure. Level of evidence: Retrospective analytical study of longitudinal temporality. Level III.